Dengue in Pune city, India (2017–2019): a comprehensive analysis - Arankalle, Vidya; Shrivastava, Shubham; Kulkarni, Ruta; Patil, Rahul; Tiraki, Divya; Mankar, Sanjay; Taru, Rohini Mahesh; Lavange, Raj; Diwan, Arundhati; Lalwani, Sanjay; Mishra, AkhileshChandra (Frontiers in Public Health, 2024)
Objectives: To understand the dynamics of dengue disease with special reference to (1) age(2) primary/secondary infections (3) serostatus and (4) serotypes examined during three consecutive years. Methods: During 3 dengue seasons (2017-19), NS1/IgM ELISAs were used for dengue diagnosis in one of the 15 administrative wards of Pune City, India. Predefined symptoms were recorded at the time of diagnosis/hospitalization. IgG-capture ELISA (Panbio) was used to differentiate primary/secondary infections. DENV serotypes were determined for 260 viral RNA-positive patients. Results: During the three years, 3014/6786 (44.4%, 41.4-49.9%) suspected cases were diagnosed as dengue. Use of either NS1 or IgM would have missed 25.5% or 43% of the confirmed dengue cases respectively. Notably, a higher proportion of secondary dengue cases remained mild while a substantial proportion of primary infections developed warning signs. The symptoms among Dengue/non-dengue patients and primary/secondary infections varied and influenced by age and serostatus. The number and proportion of dengue serotypes varied yearly. A remarkable decline in dengue cases was observed during the COVID-19 pandemic years. Conclusions: A substantial proportion of primary and secondary dengue patients progress to warning signs/severity or mild infection respectively, underscoring the possible role of non-ADE mechanisms in causing severe dengue that requires hospitalization. Both NS1 and IgM should be used for efficient diagnosis.